1980
DOI: 10.1007/bf00504531
|View full text |Cite
|
Sign up to set email alerts
|

Complete blockade by phenoxybenzamine of ?1- but not of ?2-vascular receptors in dogs and the effects of propranolol

Abstract: In pithed dogs pressor responses to phenylephrine were completely inhibited 1 h after phenoxybenzamine 20 mg/kg i.v., but those to norepinephrine were only partially inhibited. The pressor effects of norepinephrine in phenoxybenzamine-treated animals were inhibited by yohimbine, 2.0 mg/kg i.v., but not by prazosin, 0.5 mg/kg i.v. In animals treated with phenoxybenzamine, 20 mg/kg i.v., plus propranolol, 5.0 mg/kg i.v., the partially restored pressor response to epinephrine, and the responses to norepinephrine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

1982
1982
1993
1993

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(14 citation statements)
references
References 17 publications
3
11
0
Order By: Relevance
“…Although phenoxybenzamine is relatively selective for al-adrenoceptors (Dubocovich & Langer, 1972;Doxey et al, 1977;Constantine & Lebel, 1980), at the doses used in the present study (0.5-1.1 mg kg-') it would be expected to produce a2-adrenoceptor blockade in addition (Hamilton et al, 1981). It has been suggested that drugs which are selective postsynaptic aradrenoceptor antagonists (such as indoramin and prazosin) are less likely to increase heart rate in clinical use, as the negative feedback inhibition of NA release mediated by presynaptic a2-adrenoceptors is left intact (Hoffman & Lefkowitz, 1980).…”
Section: Discussionmentioning
confidence: 71%
“…Although phenoxybenzamine is relatively selective for al-adrenoceptors (Dubocovich & Langer, 1972;Doxey et al, 1977;Constantine & Lebel, 1980), at the doses used in the present study (0.5-1.1 mg kg-') it would be expected to produce a2-adrenoceptor blockade in addition (Hamilton et al, 1981). It has been suggested that drugs which are selective postsynaptic aradrenoceptor antagonists (such as indoramin and prazosin) are less likely to increase heart rate in clinical use, as the negative feedback inhibition of NA release mediated by presynaptic a2-adrenoceptors is left intact (Hoffman & Lefkowitz, 1980).…”
Section: Discussionmentioning
confidence: 71%
“…If one combines the observations of Constantine and Lebel (1980), that phenoxybenzamine is a more powerful postjunctional aj than postjunctional a 2 -receptor-blocking agent, with the recent observations of Holtz et al (1982), that coronary vasoconstriction is mediated by both <*i and a 2 postjunc- • % = 100 (phenoxybenzamine -control)/control. n = 7; mean ± 1 SEM.…”
Section: Discussionmentioning
confidence: 98%
“…To resolve the question, experiments were carried out in which tissues were pre-exposed to the irreversible antagonist, phenoxybenzamine, a drug that is selective for ac-adrenoceptors (Dubocovich & Langer, 1974;Constantine & Lebel, 1980); a concentration was chosen that reduced the contractile response to stimulation by approximately two thirds. In the aorta, the phenoxybenzamine treatment changed neither pre-nor postsynaptic effects of rauwolscine and prazosin, further confirming the olnature of the responses in that tissue.…”
Section: Discussionmentioning
confidence: 99%